Synthesis, characterization and evaluation of the photocatalytic properties of WO3 obtained through the polyol method - De Carvalho Neto, Alberto Gonçalves Vieira [UNESP]; Rissato, Sandra Regina [UNESP]; De Carvalho, Heloane Andrade Vieira [UNESP]; Favaro, Silvia Luciana; Radovanovic, Eduardo; Pellosi, Diogo Silva; Fortes, João Paulo [UNESP]; Dos Santos, Dayse Iara [UNESP]; Saeki, Margarida Juri [UNESP] (FapUNIFESP (SciELO), 2021)
This work shows a synthetic route mediated by tetraethylene glycol (P. E. 325 ° C) in which tungstic acid is used as the starting material. The formation of a stable blue suspension was observed during the course of the reaction. The size of the particles depends on the synthesis time, and particles of size around 400 nm were obtained after 15 minutes of reaction in tetraethylene glycol. The particulate materials were then annealed at different temperatures: 150 °, 350 ° C, 500 ° C and 800 ° C, and characterized by TGA/DSC, DRX, FT-RAMAN, MEV, UV-VIS optical spectroscopy and N2 adsorption at 77K. It was observed that the synthesis provided WO3 under orthorhombic phase that evolved to monoclinic after heat treatment at a temperature equal to or greater than 350 ° C. The morphological characterization indicated the formation of ovoids parti-cles when treated at temperatures around 500 ° C, a temperature from which the surface area decreases dra-matically. The photocatalytic activity for the degradation of rhodamine B (rhB, 10 mg.L-1) was evaluated under ultraviolet irradiation (6 Watts). Greater activity was found for the material treated at 500 ° C, with total discoloration after 180 minutes in the presence of 10 mg of this catalyst.
Síntese, caracterização e avaliação das propriedades fotocatalíticas do WO3 obtido através do método poliol
Keywords: Photocalysis; Polyol method; Rhodamine B; Tungsten trioxide